2020
DOI: 10.1101/2020.05.07.20085365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

THE COVID-19 FORECAST IN NORTHWEST SYRIA: The Imperative of Global Action to Avoid Catastrophe

Abstract: for their valuable and constructive suggestions during the planning and development of this research work. Their willingness to give their time so generously have been very much appreciated.Introduction: There is limited research on how the COVD-19 pandemic will affect countries with weakened health systems and particularly those in conflict. Syria's protracted conflict has strained its health systems and caused fragmentation. In this study, we focus on northwest (NW) Syria, where recent violence has driven al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Studies with patient populations[17] report lower incidence rates compared to populations in congested settings [18, 19, 22-24]. However, the incidence risk varies among the different regions of origin of those infected (0·21-2·08%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies with patient populations[17] report lower incidence rates compared to populations in congested settings [18, 19, 22-24]. However, the incidence risk varies among the different regions of origin of those infected (0·21-2·08%).…”
Section: Resultsmentioning
confidence: 99%
“…[22, 23] Irvine et al found the speed of transmission in confined detention centres to be dependent on the facility size, starting with five infected individuals at baseline, where smaller facilities of 50 detainees reach the peak of infections earlier (day 19) than larger ones of 1000 detainees (day 69), assuming a moderate reproduction number of R(0)=3·5. [24] This may be emphasised by the incidence risks of the modelling studies [22-24] plotted in figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations